2022
DOI: 10.21873/invivo.12983
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Re-irradiation With Carbon-ion Radiotherapy for Pelvic Recurrence of Rectal Cancer After Preoperative Chemoradiotherapy: A Retrospective Analysis

Abstract: Background/Aim: Previous evaluation of the safety and clinical efficacy of re-irradiation for pelvic recurrence of rectal cancer after preoperative chemoradiotherapy (PCRT) and rectal surgery is insufficient. We evaluated the safety and efficacy of re-irradiation with carbon-ion radiotherapy (C-ion RT) for pelvic recurrence of rectal cancer after PCRT. Patients and Methods: We reviewed the medical records of patients treated with C-ion RT between August 2011 and December 2021 and analyzed the data of seven con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 28 publications
0
5
1
Order By: Relevance
“…Therefore, our cohort might have more treatment-resistant, aggressive biological recurrent tumors than previous reports. In addition, the median GTV (26.1 cm 3 ) of ours was slightly larger than those of SABR (13.4 cm 3 ) and CIRT (15.6 cm 3 ) studies [ 5 , 25 ] ( Table 1 ). As a result, we considered that the clinical outcomes in our study were slightly lower than those of photon SABR and CIRT.…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…Therefore, our cohort might have more treatment-resistant, aggressive biological recurrent tumors than previous reports. In addition, the median GTV (26.1 cm 3 ) of ours was slightly larger than those of SABR (13.4 cm 3 ) and CIRT (15.6 cm 3 ) studies [ 5 , 25 ] ( Table 1 ). As a result, we considered that the clinical outcomes in our study were slightly lower than those of photon SABR and CIRT.…”
Section: Discussioncontrasting
confidence: 61%
“…Shiba et al . demonstrated reirradiation with CIRT for seven patients with LRRC after preoperative chemoradiotherapy [ 25 ]. They stated that 2-year OS, LC and PFS rates were 100, 83.3 and 28.6%, respectively (the median follow-up period was 30.9 months).…”
Section: Discussionmentioning
confidence: 99%
“…In cases where the tumor is in close proximity with the intestinal tract but does not directly invade the tumor, recent efforts have expanded the indication of CIRT by physically separating the tumor from the surrounding organs with high risk of irradiation adverse effects using spacer insertion before CIRT [ 22 , 23 ]. However, this spacer cannot be used when the recurrent lesion has directly invaded the organs at risk of irradiation adverse effects, as in this case owing to the increased risk of recurrent cancer seeding and infectious complications associated with intestinal tract injury during spacer placement surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Late phase complications, such as spacer-related infection and gastrointestinal perforation, require removal of the ePTFE spacer. Shiba et al [29] reported ePTFE spacer-related infection, resulting in colon perforation that was observed 58 months after the initiation of PT, and they underwent surgical removal of the ePTFE spacer. We removed the ePTFE spacer in eight patients who experienced severe late-phase complications.…”
Section: Discussionmentioning
confidence: 99%